A member of a gene family on Xp22.3, VCX-A, is deleted in patients with X-linked nonspecific mental retardation - Fukami, Maki; Kirsch, Stefan; Wöginger, Simone; Richter, Alexandra; Benes, Vladimir; Franco, Brunella; Muroya, Koji; Rao, Ercole; Merker, Sabine; Niesler, Beate; Ballabio, Andrea; Ansorge, Wilhelm; et al. (The American journal of human genetics, 2000)
X-linked nonspecific mental retardation (MRX) has a frequency of 0.15% in the male population and is caused by defects in several different genes on the human X chromosome. Genotype-phenotype correlations in male patients with a partial nullisomy of the X chromosome have suggested that at least one locus involved in MRX is on Xp22.3. Previous deletion mapping has shown that this gene resides between markers DXS1060 and DXS1139, a region encompassing ∼1.5 Mb of DNA. Analyzing the DNA of 15 males with Xp deletions, we were able to narrow this MRX critical interval to ∼15 kb of DNA. Only one gene, VCX-A (variably charged, X chromosome mRNA on CRI-S232A), was shown to reside in this interval. Because of a variable number of tandem 30-bp repeats in the VCX-A gene, the size of the predicted protein is 186-226 amino acids. VCX-A belongs to a gene family containing at least four nearly identical paralogues on Xp22.3 (VCX-A, -B, -B1, and -C) and two on Yq11.2 (VCY-D, VCY-E), suggesting that the X and Y copies were created by duplication events. We have found that VCX-A is retained in all patients with normal intelligence and is deleted in all patients with mental retardation. There is no correlation between the presence or absence of VCX-B1, -B, and VCX-C and mental status in our patients. These results suggest that VCX-A is sufficient to maintain normal mental development.
Gesehen am 25.03.2021